CARACTERÃSTICAS AGRONÃ”MICAS E PRODUTIVIDADE DE GRÃƒO DE CULTIVARES DE SOJA - Lemos, Leandro Borges; Farinelli, RogÃ©rio; Cavariani, ClÃ¡udio; Recco, Paulo CÃ©sar; Zapparoli, Rodolfo Alexandre; Cruciol, JoÃ£o Henrique (REVISTA DE AGRICULTURA, 2015)
CARACTERÃSTICAS AGRONÃ”MICAS E PRODUTIVIDADE DE GRÃƒO DE CULTIVARES DE SOJA